2017
DOI: 10.1073/pnas.1608877114
|View full text |Cite
|
Sign up to set email alerts
|

Response time in economic games reflects different types of decision conflict for prosocial and proself individuals

Abstract: Behavioral and neuroscientific studies explore two pathways through which internalized social norms promote prosocial behavior. One pathway involves internal control of impulsive selfishness, and the other involves emotion-based prosocial preferences that are translated into behavior when they evade cognitive control for pursuing self-interest. We measured 443 participants' overall prosocial behavior in four economic games. Participants' predispositions [social value orientation (SVO)] were more strongly refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 53 publications
17
76
1
Order By: Relevance
“…Then, they showed that the increasing difference in giving between the two games was produced mostly by a rapid decrease in giving in the DG ( Fig 1B ), rather than the increase in the UG ( Fig 1A ), among those with the thicker DLPFC. Comparable results were also reported in other studies [ 27 , 39 ]. The second purpose of our study is to critically test the two predictions depicted in Fig 1A and 1B using the CRT as an alternative measure of cognitive control.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Then, they showed that the increasing difference in giving between the two games was produced mostly by a rapid decrease in giving in the DG ( Fig 1B ), rather than the increase in the UG ( Fig 1A ), among those with the thicker DLPFC. Comparable results were also reported in other studies [ 27 , 39 ]. The second purpose of our study is to critically test the two predictions depicted in Fig 1A and 1B using the CRT as an alternative measure of cognitive control.…”
Section: Introductionsupporting
confidence: 92%
“…According to the intuitive prosociality model of human cooperation [ 22 25 ], prosocial choices are made intuitively, while selfish choices are made when the intuitive drive for prosocial choices is cognitively suppressed through deliberative scrutiny of the immediate incentives of the situation. Earlier studies [ 26 , 27 ] that compared giving in the DG and UG in terms of the cortical thickness of the dorsolateral prefrontal cortex (DLPFC), a region of the brain that is considered responsible for cognitive control, provided support for the suppression of intuitive prosocial drive account of the DG–UG difference in giving.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been argued that RT data cannot be used as evidence for intuitive/deliberative processes, since they are sensitive to the particular choice problems used by the researchers 7,16,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Presumably, habitual cooperators feel little conflict about cooperating with strangers and hence they need little time to reach a decision. On the other hand, the inverse is true for individuals with strong preferences to defect (i.e., those with individualistic or completive orientations) [42]. In summary, people feel less conflicted (and decide more quickly) when they make decisions that are in line with their pre-existing preferences and habitual behavior.…”
Section: Correlational Decision Time and Feelings Of Conflictmentioning
confidence: 99%